The epidemiology and gene mutation characteristics of pyrazinamide-resistant Mycobacterium tuberculosis clinical isolates in Southern China - Nan Wang; Fanrong Meng; Li Deng; Ling Wu; Yu Yang; Hua Li; Yuanjin Chen; Zeyou Wei; Bei Xie; Lan Gong; Qun Niu; Jie Lei; et al. (Emerging Microbes and Infections)
This study investigates the epidemic trend of pyrazinamide (PZA)-resistant tuberculosis in Southern China over 11 years (2012–2022) and evaluates the mutation characteristics of PZA resistance-related genes (pncA, rpsA, and panD) in clinical Mycobacterium tuberculosis (M. tuberculosis) isolates. To fulfil these goals, we analyzed the phenotypic PZA resistance characteristics of 14,927 clinical isolates for which Bactec MGIT 960 PZA drug susceptibility testing (DST) results were available, revealing that 2,054 (13.76%) isolates were resistant to PZA. After evaluating the annual variation in the PZA resistance rate among tuberculosis cases in this region, it was observed that it decreased from 37.21% to 6.45% throughout the initial 7 years (2012–2018) and then increased from 8.01% to 12.12% over the subsequent 4 years (2019–2022). Sequences of pncA were obtained from 402 clinical M. tuberculosis complex isolates. For rpsA and panD, sequences were obtained from 360 clinical M. tuberculosis complex isolates. Mutations in pncA were found in 8 out of 223 PZA-sensitive isolates (3.59%) and 105 of 179 (58.66%) PZA-resistant isolates. Conversely, non-synonymous mutations in rpsA were identified in 5 of 137 (3.65%) PZA-resistant isolates, whereas the mutation ratio of rpsA among PZA-sensitive isolates was high at 14.03% (31/221). This difference in the rpsA mutation rate was statistically significant (P = 0.001, chi-square test). No panD mutations were observed in the 137 PZA-resistant isolates, whereas two PZA-sensitive isolates harboured point mutations in panD, including one nonsense mutation (C433 T) and another C-69 T mutation. These findings indicate that rpsA and panD may not significantly contribute to the development of PZA resistance in clinical M. tuberculosis isolates.